IMPROVING THE QUALITY OF SOCIAL STUDIES LEARNING THROUGH INQUIRY LEARNING MODEL USING ADVENTURE BOARD MEDIA - Ardika, Balla; Widodo, Susilo Tri (Universitas Negeri Semarang, 2020)
This study aimed to develop the learning media of tribe-culture comic (kokuya) at fourth grade elementary school students.The subject of this research were the fourth grade students at Petung 2 elementary school, Pakis District, MagelangRegency. The study was research and development (R&D). This research method is to develop and validate products ineducation and learning. Data collection techniques used were observation, interviews, questionnaires, tests, anddocumentation. The final data analysis uses t-test and n-gain. The results of the study showed that kokuya learning mediacan be used in learning based on expert judgment of 75% and media expert at 90.9%, as well as the results of t-testcalculations where t count <t-abel is - 11.4388 and n-gain 0.52 included in the medium category. Student learningoutcomes increased from pretest by 71.25 increased in posttest by 86.25. It can be concluded that the learning media oftribes and cultural comics (kokuya) is very feasible and effective to be used in improving the learning outcomes of civicslearning especially for the material about tribes and cultural in Indonesian.